ON THE COMPILATION OF LARGE-SCALE ENVIRONMENTAL MAPS (GOLD PLACER MINING AREAS AS AN EXAMPLE) - Mirzekhanova Z.G.; Debelaya I.D. (My University, 2001)
A technique to generate integrated large-scale environmental maps of territories is put forward. It is based on analysis of the correlation between the ability of the natural environment to sustain the pressure of economic growth and the impact of human activities that cause environmental problems varying in the degree of acuteness. The principles for construction of maps of this type are presented and the legend is put forward. The map conveys environmental and socio-economic information: inventory of the territory, assessment, forecast, and recommendations. These principles and approaches one can apply during environmental and geographic surveying. They can provide the basis for compilation of integrated ecology maps in environmental impact statements at the feasibility level of mining projects.